The application of section 105 of the TAA and the tax court's jurisdiction to review - De Clerk, Jana (University of the Witswatersrand, Johannesburg, 2024)
Section 105 of the Tax Administration Act 28 of 2011 sets out the forum of disputing an assessment or decision taken by the South African Revenue Service. This section provides that a taxpayer who wishes to dispute an assessment, or a ‘decision’ as described in s 104 of the Tax Administration Act, may only do so in accordance with the dispute resolution procedure contained in the Tax Administration Act, unless a High Court directs otherwise. Therefore, before a tax matter can be heard by the High Court, a directive first needs to be obtained. The wording of s 105 is deceptively simple, however, it is exactly its brevity which has been the cause of significant ambiguity and uncertainty amongst taxpayers, as illustrated in a host of judgments recently handed down by the Supreme Court of Appeal. An area of particular uncertainty is the scope and application of s 105 in the context of review applications brought under the Promotion of Administration Justice Act 3 of 2000 and the principle of legality. This research report seeks to untangle this web of ambiguity and endeavours to define and interpret the correct scope of s 105, particularly how it can be reconciled with the Promotion of Administrative Justice Act and the Constitution of the Republic of South Africa, 1996. In conclusion, it is argued that s 105 cannot be interpreted to apply to applications for judicial review on the basis that the Tax Court lacks jurisdiction under these circumstances. Furthermore, the quality of exceptionality introduced by case law is flawed and the omission of this standard from the wording of the section arguably implies that it was not the intention of the legislature that this standard be satisfied by taxpayers. However, it is ultimately the view of the author that the Constitutional Court's intervention is imperative to elucidate the parameters of s 105 and to establish the threshold which must be satisfied by taxpayers where this section indeed finds application.
Research report submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg
Keywords: Tax Administration; South African Revenue Service; Taxpayer; Section 105; TAA; Tax court; UCTD; SDG-8: Decent work and economic growth